Spatio-temporal dynamics of visceral leishmaniasis transmission in a highly endemic region of Brazil - Nunes Ribeiro, Caíque Jordan; Ribeiro, Bianca Vanessa dos Santos; Santos, Allan Dantas dos; Santos, Márcio Bezerra; Santos, Priscila Lima dos; Araújo, Karina Conceição Gomes Machado de; Santos, Guilherme Reis de Santana; Santana, David Vinicius dos Santos; Carneiro, Liliane Moretti; Moura, Tatiana Rodrigues de (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Brazil concentrates 96% of visceral leishmaniasis cases occurred in Americas, and Maranhão is the Brazilian state with the highest number of registered cases. Aim: to analyze the spatio-temporal dynamics of visceral leishmaniasis transmission in a Brazilian region with high endemicity between 2009 to 2017. Design: We carried out an ecological and time series study using spatio-temporal analysis techniques. A time-trend analysis was performed by the segmented linear regression. High-risk clusters were identified through spatial autocorrelation (Moran’s global and local indexes) and space-time scan statistics. Results: There were 5,128 visceral leishmaniasis cases, and it was observed increasing trends of new cases in the general population, among men, adults ≥20 years old, especially ≥60 years old. VL-HIV coinfection, mortality and lethality were crescent. Spatial analysis revealed intense visceral leishmaniasis transmission in almost the entire state and high-risk priority areas. Implications: Visceral leishmaniasis is in a substantial geographical expansion, demonstrating that the surveillance policies need to be reformulated.